Creating and contesting hierarchy: the punitive effect of sanctions in a horizontal system - Alexandra Hofer (Revista CIDOB d'Afers Internacionals, 2020)
Sanctions are presented as a form of international punishment that not only stigmatises the target, but creates a hierarchy between those who impose punishment and those punished. Such practices go against the principle of sovereign equality and contradict the horizontal structure of the international system. Drawing on the literature on stigma management and resentment, this paper argues that when states react to sanctions, they respond not only to the imposition of stigma, but also to the inferior position in which they are placed. Targets may resent the position of authority adopted by the sanctioners. This may in turn motivate them to contest the status quo upon which sanctioners justify their authority, thereby reasserting the norms and corresponding practices they believe should be prioritized.